THE RELATIONSHIP BETWEEN MOTOR COORDINATION AND PHYSICAL PERFORMANCE IN YOUNG VOLLEYBALL PLAYERS IN ALBANIA (University Arena, 2025)
This study explores the relationship between motor coordination and physical performance in a sample of 10.7-year-old children (N = 33) who regularly participate in volleyball training in Tirana, Albania. The assessment tools included two subtests from the Körperkoordinationstest für Kinder (KTK): the Plate Movement test and the Lateral Jumping test, which evaluate dynamic coordination and lateral agility, respectively. Physical performance was measured using the Standing Long Jump test, which assesses lower-body explosive strength, and the 20-meter sprint test, which reflects linear speed. The findings reveal a statistically significant positive correlation between the Standing Long Jump and both coordination tests–KTK Plate Movement (r = 0.531, p = 0.028) and KTK Lateral Jumping (r = 0.641, p = 0.006)–indicating that children with higher coordination levels tend to perform better in tasks requiring explosive leg power. These results suggest a strong link between coordination and lower-body strength, which is crucial for volleyball-specific movements such as jumping and quick directional changes. In contrast, the correlations between the 20-meter sprint test and the coordination tests were moderate but not statistically significant–KTK Plate Movement (r = –0.471, p = 0.056) and KTK LateralJumping (r = –0.413, p = 0.099). These negative correlations suggest a trend where better coordination might be associated with faster sprint performance; however, the lack of statistical significance may be due to sample size or variability in sprint mechanics among children at this developmental stage.